Collaborative control for in situ monitoring of molten pool in selective laser melting - Lin, Xin; Liu, Bing; Shen, Anchao; Cui, Zhiwei; Zhu, Kunpeng (Frontiers in Mechanical Engineering, 2023)
In-situ monitoring during selective laser melting (SLM) process is a promising solution to improve defects and the quality of as-built parts. However, the existing monitoring platform installed in the forming chamber still lacks collaborative with the SLM device, which cannot realize real-time and accurate signal acquisition from a close distance and multiple angles in the whole printing process. In this paper, the off-axis monitoring platform is constructed which is driven by multiple motors and moving in conjunction with the scraper and laser. A fuzzy control based velocity optimization is proposed to avoid shock affecting the imaging quality of CMOS camera as well as the collision of the scraper and laser. The error between the current position of the monitoring platform and the target position of the molten pool is utilized as the input of the fuzzy controller. Then the parameter values of the PID controller of the stepping motor are dynamically adjusted. ADAMS and SIMULINK co-simulation is conducted to verify the feasibility of the fuzzy algorithm. Finally, the collaborative motion experiment and the response process of each module are tested. The results show that the response speed of the system is improved by about 49.6% after the speed curve is optimized. The speed of the motor at the beginning is decreased by about 12.6%, which avoids excessive acceleration of the motor to cause losing steps or overshoot. The response time of each motor is ahead of schedule about 31.8%, which meets the requirements of motion response beat in SLM device.